2021
DOI: 10.1186/s12885-021-07994-3
|View full text |Cite
|
Sign up to set email alerts
|

PCNA-associated factor (KIAA0101/PCLAF) overexpression and gene copy number alterations in hepatocellular carcinoma tissues

Abstract: Background PCNA-associated factor, the protein encoded by the KIAA0101/PCLAF gene, is a cell-cycle regulated oncoprotein that regulates DNA synthesis, maintenance of DNA methylation, and DNA-damage bypass, through the interaction with the human sliding clamp PCNA. KIAA0101/PCLAF is overexpressed in various cancers, including hepatocellular carcinoma (HCC). However, it remains unknown whether KIAA0101/PCLAF overexpression is coupled to gene amplification in HCC. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…More and more studies have confirmed the functional interaction between PCLAF and tumors ( 8 , 10 , 11 , 52 , 53 ). Numerous studies have performed immunohistochemical analysis of various tumor tissues, which strongly suggest that PCLAF is highly expressed in a variety of tumor tissues and may serve as a pan-cancer prognostic biomar ker ( 13 , 42 , 43 , 46 50 , 54 , 55 ). Yet, the pathogenesis of PCLAF in different tumors is still unclear, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have confirmed the functional interaction between PCLAF and tumors ( 8 , 10 , 11 , 52 , 53 ). Numerous studies have performed immunohistochemical analysis of various tumor tissues, which strongly suggest that PCLAF is highly expressed in a variety of tumor tissues and may serve as a pan-cancer prognostic biomar ker ( 13 , 42 , 43 , 46 50 , 54 , 55 ). Yet, the pathogenesis of PCLAF in different tumors is still unclear, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 375 , 376 Furthermore, upregulated PCNA is associated with various digestive system tumors including colorectal carcinoma, ESCC, and HCC (Table 5 ). 377 , 378 , 379 …”
Section: Dna Replication Disease and Therapymentioning
confidence: 99%
“…375,376 Furthermore, upregulated PCNA is associated with various digestive system tumors including colorectal carcinoma, ESCC, and HCC (Table 5). [377][378][379] PCNA is a critical factor in DNA replication and DNA damage repair. Hence, PCNA is a target for designing antiproliferation and anticancer drugs.…”
Section: Pcna As Prognostic Markers and The Target For Therapymentioning
confidence: 99%
“…Gene integrated bioinformatics analysis indicates that PCLAF is one of the core genes associated with HCC[ 52 ]. PCLAF mRNA levels are increased in HCC[ 53 ]. A recent study has shown that PCLAF is involved in the microvascular invasion in HCC by activating epithelial-mesenchymal transition[ 13 ].…”
Section: Pclaf Contributes To the Development Of Gi Tumorsmentioning
confidence: 99%